Establishing a Business in Ukraine - the Initial Regulatory Organizational and Legal Aspects for Polish Entrepreneurs - Beata Glinkowska; Viacheslav Chebotarov (Comparative Economic Research. Central and Eastern Europe, 2019)
The inspiration to create this summary was research carried out on the Polish-Ukrainian internationalization of business activity conditions and their models. The article contains conclusions based on the authors' interviews with Ukrainian businessmen and government officials, as well as an analysis of legal acts related to establishing a business in Ukraine by members of the Polish business community. A reference to fundamental regulations is presented. The research shows that serious legal easements for starting a business in Ukraine have occurred. This is the first step towards building a positive atmosphere. However, there are many factors which often discourage Polish entrepreneurs to initiate foreign expansion towards Ukraine and, on this basis, beyond its borders. The governments of both countries should pay attention to them. In this context, the article contains initial provisions for improving the legislative base of Ukraine in the field of internationalization. For Polish entrepreneurs, the basic recommendations for establishing a business in Ukraine are justified.
Keywords: F02; F23; 330; world's goods and raw materials markets; internationalization; foreigneconomic activity; enterprise; motives; barriers; business; establishing a business; foreign direct investment